2022
DOI: 10.1038/s41598-022-23602-1
|View full text |Cite
|
Sign up to set email alerts
|

Real-world clinical effectiveness and sustainability of universal bloodborne virus testing in an urban emergency department in the UK

Abstract: Innovative testing approaches and care pathways are required to meet HIV, hepatitis B (HBV) and hepatitis C (HCV) elimination goals. Routine testing for blood-borne viruses (BBVs) within emergency departments (EDs) is suggested by the European Centre for Disease Prevention and Control but there is a paucity of supporting evidence. We evaluated the introduction of routine BBV testing in EDs at a large teaching hospital in northern England. In October 2018, we modified the electronic laboratory ordering system t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…The analysis evaluated the cost-effectiveness of ED testing in two locations; Leeds Teaching Hospitals NHS Trust (LTHT), and Guys and St. Thomas' NHS Foundation Trust (GSTT) in London [13,14]. In both EDs, the electronic patient record systems were modified to include a HBV and HCV test for adults, unless they opt-out.…”
Section: Model Analyses and Decision Problemmentioning
confidence: 99%
See 3 more Smart Citations
“…The analysis evaluated the cost-effectiveness of ED testing in two locations; Leeds Teaching Hospitals NHS Trust (LTHT), and Guys and St. Thomas' NHS Foundation Trust (GSTT) in London [13,14]. In both EDs, the electronic patient record systems were modified to include a HBV and HCV test for adults, unless they opt-out.…”
Section: Model Analyses and Decision Problemmentioning
confidence: 99%
“…Patients requiring linkage to care in both EDs were contacted by various means, including phone calls, text messages, and letters to their home and registered GP. Full details are available in the original testing publications [13,14]. Specialist outreach nurses or teams working with the homeless were also informed of those requiring linkage to care.…”
Section: Prevalence and Linkage To Carementioning
confidence: 99%
See 2 more Smart Citations
“…Patient autonomy would be maintained by using systems that allow individuals to opt out of implicit consent [26]. A recent experience in England showed that the introduction of routine bloodborne virus (BBV) testing in the ED, modifying the electronic laboratory ordering system to reflect opt-out for testing for all ED attendees aged 16-65 years who had a routine blood test, proved feasible and effective in identifying active BBV infections, and showed a seroprevalence of 0.4% for HIV infection [27]. Another important barrier may be the fact that HIV care in the ED today does not routinely occur for AIDS-indicative illnesses [28][29][30], which may lead the physician not to perceive HIV as an important problem.…”
Section: Discussionmentioning
confidence: 99%